PROBLEMA PELAKSANAAN PROSES PEMBELAJARAN PENDIDIKAN KESETARAAN PROGRAM PAKET C DI PKBM RIAU CEKATAN KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Ira Rahmayanti; Titi Maemunaty; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to know the activities carried out in the performance of the learning process at PKBM Riau Cekatan and to know the problem of carrying out the learning process of the equal education from C package programme at PKBM Riau Cekatan Tuah Karya sub-district Tampan Pekanbaru city. Type of this research engage a descriptive research with qualitative approach which consist a variable that is problem of carrying out the learning process of the equal education from C Package programme at PKBM Riau Cekatan Tuah Karya sub-district Tampan Pekanbaru city. Fruition of this research build upon 2 indicators, 6 subs-indicators, 13 dimentions about problem of carrying out the learning process of the equal education from C package programme based accumulation data technic, researcher make a interview guidance by 40 questions. Result of debate from study group, facilities and infrastructure, text book for learning, method module for learning and difficulity for understand the module in self-activity is problem of carrying out the learning process of the equal education from C package programme in PKBM Riau Cekatan.Keyword: Problem, Performance Process of Learning, Equal Education From C Package Programme